1993
DOI: 10.1021/jf00035a060
|View full text |Cite
|
Sign up to set email alerts
|

Soil metabolism of the herbicide isoxaben in winter wheat crops

Abstract: Winter wheat fields were treated with the herbicide isoxaben after sowing. Trials were made in 1990-1991 and 1991-1992. The main isoxaben soil metabolite was demethoxyisoxaben (N-[3-(l-ethyl-lmethylpropyl)isoxazo1-5-yll-2-hydroxy-6-methoxybenzamide), Le., the monodemethoxylation product of isoxaben. 5-Isoxazolone (34 l-ethyl-l-methylpropyl)isoxazolin-5-one) was the second main isoxaben metabolite. When 5-aminoisoxazole (5-amino-3-(l-ethyl-l-methylpropyl)isoxazole) was detected in soil, it always was a t very l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…This growth could explain why the compound did not accumulate in the medium. However, as previously reported,6 the presence of demethoxyisoxaben and of 2‐hydroxy‐6‐methoxybenzamide in soil treated with isoxaben suggests a modification of the phenyl ring before hydrolysis of the amide bond of isoxaben. This hypothesis is supported by the study of a chloridazon‐degrading bacteria transforming metamitron to 2‐dihydroxy‐metamitron which was then cleaved by meta ‐fission 20…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…This growth could explain why the compound did not accumulate in the medium. However, as previously reported,6 the presence of demethoxyisoxaben and of 2‐hydroxy‐6‐methoxybenzamide in soil treated with isoxaben suggests a modification of the phenyl ring before hydrolysis of the amide bond of isoxaben. This hypothesis is supported by the study of a chloridazon‐degrading bacteria transforming metamitron to 2‐dihydroxy‐metamitron which was then cleaved by meta ‐fission 20…”
Section: Resultssupporting
confidence: 72%
“…In their previous study, Rouchaud et al 6 also reported the presence of 3‐(1‐ethyl‐1‐methylpropyl) isoxazol‐5‐ylamine in soil extract, but the compound did not accumulate and they therefore considered the possibility of an unusual mechanism for amide hydrolysis with 5‐isoxazolone accumulation. Our results suggest that 3‐(1‐ethyl‐1‐methylpropyl)isoxazol‐5‐ylamine could be an important intermediary product of the microbial degradation of isoxaben in soil.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The herbicidal activity of isoxaben was not lost following shallow incorporation into the soil, and> 75% of the compound remained in the top 0 to 7.5 em of the soil (Colbert and Ford 1987). Soil degradation of isoxaben is primarily through microbial activity (Rouchaud et al 1993). Solar breakdown of isoxaben has also been reported in aquatic systems (Mamouni et al 1992).…”
Section: Introductionmentioning
confidence: 98%
“…Onto each plot, one (and always the same) of the different organic fertilizers treatments schemes 1 to 5 was applied repeatedly during this 30 years period In previous work we observed that the soil persistence of the herbicide diflufenican (1; N-(2,4-difluorophenyl)-2-[3-(trifluoromethyl)phenoxy]-3-pyridinecarboxamide) in winter wheat crop was increased when one of the organic fertilizers green manure, pig slurry or cow manure had been applied some days before sowing. 1 The organic amendments slowed down the whole diflufenican soil metabolism, as the soil concentrations of its herbicide metabolites 2 (2-[3-trifluoromethyl)phenoxy]-3-pyridinecarboxylic acid) and 3 (N-(2,4-difluorophenyl)-2-hydroxy-3-pyridinecarboxamide), and of its non herbicide metabolite 4 (2-hydroxy-3-carboxypyridine) were lower in the organic fertilizers treated plots than in the untreated ones. Application of the organic amendments one month before wheat sowing is frequent in the agronomy practice; especially with pig slurry, as problems exist for the elimination of the animal effluents in regions of intensive pig breeding.…”
mentioning
confidence: 96%